2012
DOI: 10.1007/s10875-012-9652-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactive Antibodies to Target Proteins are Dependent upon Oligomannose Glycosylated Epitopes in HTLV-1 Associated Neurological Disease

Abstract: Our lab recently identified a cross-reactive antibody response between human T-lymphotropic virus type-1-p24-(gag) (HTLV-1-p24-(gag)) and peroxiredoxin-1 (PrX-1) as potentially contributing to the pathogenesis of HTLV-1 associated neurological disease via molecular mimicry. These targets proteins were glycosylated, yet the glycan side chains immunoreactive with the immunoglobulins were unknown. Using a combination of lectin isolation and serial enzymatic deglycosylation of glycoproteins, we determined that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…For example, a recent study showed that autoantibodies to the potassium channel KIR4.1, a glial protein, might contribute to the pathogenesis of MS. 124,125 A potential role for antibodies to the RBP hnRNP A1 in the pathogenesis of neurodegeneration in MS and HAM/TSP Data generated in our lab also indicate that antibodies to the nonmyelin compartment, specifically neurons, may contribute to the pathogenesis of MS and HAM/TSP. [11][12][13][14][126][127][128][129] Initially, submit your manuscript | www.dovepress.com Dovepress Dovepress using neuronal proteins purified from human brain, IgG isolated from HAM/TSP patients was found to immunoreact with a 33 kDa protein by Western blot. 126 Subsequently, the protein was identified as heterogeneous nuclear ribonuclear protein A1 (hnRNP A1).…”
Section: Antibodies As Contributors To Neurodegeneration and The Pathmentioning
confidence: 99%
“…For example, a recent study showed that autoantibodies to the potassium channel KIR4.1, a glial protein, might contribute to the pathogenesis of MS. 124,125 A potential role for antibodies to the RBP hnRNP A1 in the pathogenesis of neurodegeneration in MS and HAM/TSP Data generated in our lab also indicate that antibodies to the nonmyelin compartment, specifically neurons, may contribute to the pathogenesis of MS and HAM/TSP. [11][12][13][14][126][127][128][129] Initially, submit your manuscript | www.dovepress.com Dovepress Dovepress using neuronal proteins purified from human brain, IgG isolated from HAM/TSP patients was found to immunoreact with a 33 kDa protein by Western blot. 126 Subsequently, the protein was identified as heterogeneous nuclear ribonuclear protein A1 (hnRNP A1).…”
Section: Antibodies As Contributors To Neurodegeneration and The Pathmentioning
confidence: 99%
“…Previously described as a predominantly demyelinating disease, MS is now considered both a disease of inflammatory-mediated demyelination and neurodegeneration (loss or damage to neurons and axons) (Peterson and Fujinami, 2007). These pathologic features are also present in HAM/TSP, which resembles progressive forms of MS clinically, but unlike MS, has been shown to be caused by infection with HTLV-1 (Jernigan et al, 2003;Lee et al, , 2012.…”
Section: Spinal Muscular Atrophy (Sma)mentioning
confidence: 99%
“…Decreased levels of Prdx2 were seen in the cerebral spinal fluid of such AIDS patients [ 158 ]. Moreover, the presence of cross-reactive antibodies to p24-(gag) protein of another lentivirus, human T-lymphotropic virus type-1 (HTLV-1), and peroxiredoxin 1 was noted [ 159 ]. It can be speculated that scavenging of this antioxidant enzyme can also contribute to the development of virus-associated neurological disorders.…”
Section: Peroxiredoxins and Viral Infectionsmentioning
confidence: 99%